Ecoformative Pedagogical Strategies in Higher Education: Experiences at the Castro Carazo University (Costa Rica) - Acuña Rodríguez, María del Carmen (Innovaciones Educativas, 2025)
Ecoformation is understood as a life philosophy that promotes harmony in individuals' relationships with themselves, other living beings (human and nonhuman) and the planet. The general objective of this study, based on the experience of the University of Castro Carazo (Costa Rica), was to analyze the application of ecotraining in university teaching. The specific objectives were to identify the epistemological changes needed to implement Ecotraining and to compile the pedagogical strategies used by the faculty to implement it. The work presents tools for teachers and universities that want to use eco-training to respond to a planetary need: to act in the face of the crisis of the human being and the environment. Methodologically, a qualitative approach with a case study design was selected. A combination of semi-structured interviews and an anonymous virtual questionnaire was used, with the participation of a total of 120 people: teachers, administrators and university authorities. In total, 85 pedagogical practices were captured. The analysis of the results was carried out by means of eight categories defined a posteriori on the basis of the results (for each category, the number of examples mentioned is indicated in parenthesis): Different perspective on the educational act (11), emphasis on learning (9) and on the students as persons (11), planetary awareness as an axis or theme of the students' work (19), contextualized application of the careers or professions for which the student body is being trained (14), authentic assessment of learning (14), inclusion of playful activities in the courses (7), and use of technological tools (10). For each category, the examples provided by the participants are listed. In conclusion, it is necessary to transform the vision of the educational act and its elements to be coherent with eco-training, including planetary awareness. Furthermore, although the context of study is higher education, it is considered that the results can be applied to other educational levels and contexts.